Optimalisasi Potensi Ekowisata Bukit Matoa Dengan Melakukan Pemberdayaan Kelompok Sadar Wisata (POKDARWIS) Dalam Pengolahan Sampah dan Pengendalian Vektor Melalui Sosialisasi - Fitriyani; Aisyah Nur Utami Putri; Muhammad Farras Rinaldy; Mutia Hasna Khairani; Dzakhira Indria Syafitri; Nabila Tiara Rahma Dewi (Warta Pengabdian Andalas, 2025)
Ecotourism integrates natural beauty, conservation, and the welfare of local communities. Bukit Matoa, located in Padang City, West Sumatra, presents promising ecotourism potential but faces challenges related to sanitation and visitor safety. Identified issues include domestic waste accumulation, lack of firefighting infrastructure, unsafe trekking routes, and inadequate first aid facilities. An empowerment program targeting the Tourism Awareness Group, called as Pokdarwis, was conducted to address these challenges. The activities involved education on waste composting, mosquito vector control, ergonomic trekking route design, and basic firefighting techniques. The target of Socialization was cadres who were members of the Tourism Awareness Group. The activity was conducted at the Pokdarwis chairman's house in the Bukit Matoa area. The results of the socialization showed that a team was formed to improve the design of new stairs, there was planning for toilet repairs along with the cleaning responsible person, increased knowledge of cadres about how to use fire extinguishers and reducing the fire risk in ecotourism, as well as there is a plan to create a location for collecting household waste for making compost. Furthermore, continuous stakeholder engagement and program execution are recommended to optimize the site's potential.